Pengukuran Kinerja Manajemen Pendidikan dan Implementasinya Menggunakan Balance Score Cards - Septriana Murdiani; Maemunah Sa’diyah (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Balanced Scorecards (BSC) is one of the management and measurement systems used to measure the work efficiency of an institution. In Indonesia, the BSC is used as a tool for measuring the performance of higher education institutions, only a few have written about its use at the elementary and secondary school levels. Contrary to what the experts found about the poor condition of Indonesian education, the results of the BSC measurement from the study literature show the opposite condition. Is there any other meaning of these results? The success of the BSC is associated with the vision and mission of the educational institution, that's why the BSC is private and does not describe a strategy for education in general. If a benchmark of Islamic education is made and supported by longitudinal research, it will help the long-term achievement of Islamic education.